THE POWER OF METAPHOR IN SHAPING PUBLIC CONSCIOUSNESS IN UZBEK POLITICAL DISCOURSE (International Conference on Education, Psychology and Humanities, 2026)
This thesis examines the role of metaphor in shaping public consciousness in Uzbek political discourse. Metaphor is considered not only as a stylistic device but also as a cognitive and persuasive mechanism that structures political meanings, guides social perception and influences collective attitudes toward reforms, national identity and development. The study focuses on common metaphorical models used in Uzbek political language, including the nation as a family, development as a journey, reform as construction and society as a living organism. The findings show that metaphors simplify complex political processes, make abstract ideas emotionally accessible and strengthen the connection between state discourse and public values.
Keywords: metaphor, political discourse, Uzbek language, public consciousness, cognitive linguistics, persuasion, national identity, political communication.